1982
DOI: 10.1126/science.7063881
|View full text |Cite
|
Sign up to set email alerts
|

Oculoparalytic Illusion: Visual-Field Dependent Spatial Mislocalizations by Humans Partially Paralyzed with Curare

Abstract: In darkness, observers partially paralyzed with curare make large (greater thn 20 degrees) gaze- and dosage-dependent errors in visually localizing eye-level-horizontal and median planes, in matching the location of a sound to a light, and in pointing at a light. In illuminated, structured visual localization and pointing are accurate but errors in auditory-to-visual matches remain. Defects in extraretinal eye position information are responsible for all errors. The influence of extraretinal eye position infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 13 publications
(11 reference statements)
14
85
1
Order By: Relevance
“…This implies that under normal perceptual conditions the efference copy signal of eye position after the saccade plays only a minor role in transsaccadic localization; rather, transsaccadic displacement judgements and perceived visual stability are based on the evaluation of postsaccadic landmark objects. The importance of visual reference frames is also supported by earlier experiments, which indicated that in normal visual scenes, visual information dominates over eye position information in judgements of visual direction, when both signals are in conflict (Matin, Picoult, Stevens, Edwards, Young, & MacArthur, 1982;Stark & Bridgeman, 1983).…”
Section: Discussionsupporting
confidence: 63%
“…This implies that under normal perceptual conditions the efference copy signal of eye position after the saccade plays only a minor role in transsaccadic localization; rather, transsaccadic displacement judgements and perceived visual stability are based on the evaluation of postsaccadic landmark objects. The importance of visual reference frames is also supported by earlier experiments, which indicated that in normal visual scenes, visual information dominates over eye position information in judgements of visual direction, when both signals are in conflict (Matin, Picoult, Stevens, Edwards, Young, & MacArthur, 1982;Stark & Bridgeman, 1983).…”
Section: Discussionsupporting
confidence: 63%
“…Sherrington (1918), solely on the grounds that human extrinsic ocular muscles contain muscle spindles and without answering Helmholtz's contrary arguments, suggested that we use proprioceptive information from sensors in the extrinsic ocular muscles {see Milleret et al, 1985, for a review of the literature on direct and secondary central projections of ocular muscle proprioceptors). Mach (1886), Kornmuller (1931), Brindley and Merton (1960), Stevens et al (1976), Matin et al (1982) and Guthrie et al (1983) published new experiments that confirm that outflow information is used, but did not exclude a minor contribution from proprioceptors. Sherrington's view in its pure form has never had any experimental support, but Siebeck (1954) published an observation which made it probable that in one extreme situation messages from sensors in the orbit can influence the direction of things seen.…”
Section: Introductionmentioning
confidence: 91%
“…If Siebeck's subjects succeeded in sending impulses out along their oculomotor nerves, this disproves (for an extreme condition) the pure form of Helmholtz's theory. Brindley et al (1976) and Matin et al (1982) extended Siebeck's experiment to unilateral paralysis. They showed that during an attempted eye movement, things seen by an eye whose extrinsic muscles are completely paralysed by retrobulbar injection of local anaesthetic appear stationary, although, if the paralysis is incomplete, they move as predicted by Helmholtz's theory.…”
Section: Introductionmentioning
confidence: 99%
“…A parallax method showed that an eyepress displaces the eye medially in the orbit as a result of combined pressure from the finger and the lateral rectus muscle. A structured visual field reduces the perceptual effects of changed oculomotor efference (Matin et al, 1982). A pointing measure, however, shows effects of changed efference both with and without a structured visual field (Stark & Bridgeman, 1983).…”
Section: Discussionmentioning
confidence: 93%